2002
DOI: 10.1021/es0114097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surfactants on the Survival and Sorption of Viruses

Abstract: There is an increasing concern about the protection of groundwater from contamination by enteric viruses and the prevention of outbreaks of waterborne diseases. Knowledge of survivability and transport of viruses from their point of origin is necessary to determine their potential effects on the neighboring groundwater systems. The distribution of virus is, in turn, dependent on the physical and chemical compositions of the surrounding soil and subsurface systems. For the present study, we have determined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 30 publications
1
41
1
Order By: Relevance
“…The process was undoubtedly favored by the presence of divalent ions in our GW, but in other GW such a process can be favored by a pH below or equivalent to the viral isoelectric point. Major adhesion of viruses to the walls of different container materials has been already reported (7,29,40,42,45). Taylor et al (40) observed in a synthetic water-Poliovirus 2-polypropylene support system that when the pH fell below 7, 90% of the viral particles adhered to the supporting walls.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The process was undoubtedly favored by the presence of divalent ions in our GW, but in other GW such a process can be favored by a pH below or equivalent to the viral isoelectric point. Major adhesion of viruses to the walls of different container materials has been already reported (7,29,40,42,45). Taylor et al (40) observed in a synthetic water-Poliovirus 2-polypropylene support system that when the pH fell below 7, 90% of the viral particles adhered to the supporting walls.…”
Section: Discussionmentioning
confidence: 87%
“…Organic matter present in the STE might saturate sites of adsorption on the polypropylene walls, thus preventing viral adhesion. The saturation would result from a competition between the organic matter and the virus for adhesion sites (7,17,24,33). This mechanism was used to elute viruses adsorbed on membranes (27) or in protocols for concentrating viruses from water, as a lot of elution buffer contains beef extract (6,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These phages can be easily produced in large quantities (e.g., 10 15 phages in 10 L) but detected at extremely low levels (∼1 phage in 2 mL); furthermore, they are not harmful to humans and the aquatic environment. Phages are particularly useful to simulate transport and attenuation processes in saturated and un-saturated porous media, either by means of column or batch experiments in the laboratory (8,9) or field experiments in sand and gravel aquifers (10)(11)(12)(13)(14), flowing surface waters (12), waste stabilization ponds (15), or constructed wetland areas (16). Naturally occurring phages that infect fecal or patho-genic bacteria are increasingly used as contamination indicators (17).…”
mentioning
confidence: 99%
“…environmental factor affecting virus inactivation is temperature with lower inactivation rates at cold temperatures (Hurst et al 1980;Yates and Yates 1987;Yates et al 1985). The presence of natural organic matter has also shown to affect virus survival (Bixby and O'Brien 1979;Chattopadhyay et al 2002;Moore et al 1982). For water managers exploiting natural or managed groundwater resources it is essential that virus inactivation is understood at low temperatures and in the presence of natural organic matter as prolonged virus survival is conducive under these conditions.…”
Section: Introductionmentioning
confidence: 99%